Pengaruh Pemberian Perasan Belimbing Wuluh (Averrhoa bilimbi L.) Terhadap Kemampuan Fisik Mencit (Mus musculus) Yang Dipapar Asap Rokok - Agung Giri Samudra; Sari Yanti; Dwi Ani Wijayanti (STIFA Makassar, 2017)
One of the plants that are often used to maintain of our healthy body is the star fruit (Averrhoa bilimbi L.), that high contains vitamin C. Cigarette smoke contains harmful substances such as nicotine, tar, and carbon monoxide are the trigger free radicals. The purpose of this study to evaluate the effect of star fruit juice to physical ability of male mice (Mus musculus) against cigarette smoke-induced. Mice were divided into five groups (n=5/group): standard group where Garcia (1.04 mg /20 g BW), was used as standard drug and 3 test groups were given fresh juice of star fruit (0.2 mL, 0,4 mL, 0,6 mL/ 20gram BW) was used for 14 days via gavage through oral route. All groups were exposed to cigarette smoke during treated (1 cigarette per day). The physical ability was assessed on day 15-forced swimming test (FST) has been done in mice. The results showed a strong and dose-dependent prevention effect and significantly exhibited an increase in mean swim endurance time on day 15 compared to baseline (p <0.05). In conclusion, the star fruit juice possesses a protective effect.